Xanthogranulomatous Adrenalitis: A Case Report and Literature Review - Dai, Xiang; Zhang, Yuanyuan; Du, Yiqing; Lai, Shicong; Wang, Gongwei; Yu, Luping; Zhang, Xiaopeng; Xu, Tao (Frontiers in Urology, 2022)
Xanthogranulomatous adrenalitis (XGA) is a rare inflammatory condition of the adrenal glands, probably resulting from a combination of chronic infection and local bleeding. Herein, we present an exceedingly rare case of functional xanthogranulomatous adrenalitis occurring in a 44-year-old Chinese female patient. With a history of intermittent superficial infection and a high level of C-reactive protein for 6 months, she presented to the hospital without fever or flank pain. Magnetic resonance imaging revealed a 5-cm right adrenal mass, which showed iso-signal on T1WI and a slightly long signal or iso-signal on T2WI. The preoperative basal serum renin level of the patient was decreased and the aldosterone-to-renin ratio was increased. After laparoscopic radical adrenalectomy, the adrenal mass was diagnosed as xanthogranulomatous adrenalitis, which was confirmed by histological examination and immunohistochemical staining for CD68. One month after surgery, the serum renin and aldosterone to renin ratio of the patient dropped to normal levels. Our case shows that xanthogranulomatous adrenalitis may resemble functional adrenal neoplasms, both biochemically and radiologically. The most likely cause of xanthogranulomatous adrenalitis is chronic infection, especially gram-positive coccus infection. Xanthogranulomatous adrenalitis should be considered when clinical and radiological manifestations are not typical for other inflammatory diseases or adrenal neoplasms.